Ukhuwah and Friendship as Spiritual Social Capital in Improving Subjective Well-Being and Mental Health: An Integrative Conceptual Study of Islamic Perspectives - Abul A’la Al Maududdi; Fitriani Sehuwaky; Nella Ika Puspa Dewi; Fabby Azhezinova (Green Publisher Indonesia, 2026)
Modernization and urbanization have changed the patterns of social relations in society and contributed to the increase in mental health problems, especially in urban Muslim communities. The dominant clinically oriented approach to mental health is considered suboptimal without the integration of social and spiritual dimensions. This research aims to analyze the role of ukhuwah and friendship as spiritual social capital in improving the subjective well-being and mental health of the Muslim community. The method used is an integrative literature review conducted by analyzing reputable scientific publications, global health reports, and classical and contemporary Islamic literature. The results of the study show that ukhuwah strengthens social identity, spiritual solidarity, and a sense of belonging in the community, while communal gathering improves the quality of interpersonal communication and emotional support. Both form a spiritual social capital that contributes significantly to increased life satisfaction, emotional stability, and a reduced risk of mental health disorders. These findings are in line with the Harvard Study of Adult Development, which confirms that the quality of social relationships is a major predictor of long-term happiness and health. This study concludes that strengthening ukhuwah and friendship can serve as a community-based promotive-preventive strategy in the promotion of mental health within the Muslim community.